Play in School – Toward an Ecosystemic Understanding and Perspective - Skovbjerg, Helle Marie; Sand, Anne-Lene (Frontiers in Psychology, 2022)
Based on a design-based research project and long-term observations of children’s play in school, this article develops the concept of play order, which points to interaction, coherence and holistic orientation as central values for the approach to play in school. Through concrete empirical analysis, the article shows how play in school is established and maintained, and how school as context interacts with play, which is often in ways that undermine the space and opportunities play is given. Based on existing research, the article is critical of the tendency to accord a secondary role to play in school or to instrumentalize play as a didactic tool for learning. The article links to existing play theory, but at the same time develops the concept of play order, through an ecosystemic understanding, which makes it possible to look holistically at how play in school can be integrated and provided for. Considering that more and more pedagogues are working in schools and directly involved in teaching, and afterschool clubs (SFO) are increasingly handling schooling tasks, the authors of the article argue that play is worthy of recognition in both practice and theory.